2011
DOI: 10.2113/gssgfbull.182.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Migration of a synclinal depocentre from turbidite growth strata: the Annot syncline, SE France

Abstract: The Annot Sandstone turbidites of the Alpine foreland basin in SE France (Eocene-Oligocene: 40-32 Ma), provide an excellent case-study of tectono-sedimentary relations in a deepwater compressional system. The Annot outlier is a synclinal remnant previously interpreted as a static depocentre. A multi-disciplinary approach including geometrical and kinematic analyses and modelling demonstrates instead that this was a tectonically active turbidite depocentre where gentle thrust related folding controlled turbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…During this time, south of the Ecrins Massif, in the Grès d'Annot Basin, Apps [, 2004] and Salles et al . [] have shown that SW directed thrusting occurred during the deposition of the Nummulitic series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During this time, south of the Ecrins Massif, in the Grès d'Annot Basin, Apps [, 2004] and Salles et al . [] have shown that SW directed thrusting occurred during the deposition of the Nummulitic series.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, after this main E‐W deformation phase, a gently N‐S shortening probably affected the European crust around the Ecrins Massif area [ Gratier et al ., ; Gidon and Pairis , ; Salles et al ., ]. The last observed deformations are characterized by the reactivation of the Penninic Frontal Thrust as a normal fault [ Ceriani et al ., ; Tricart et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method avoids the use of cross sections as an intermediate step that can mask the real 3D geometry of geological structures (Fernández et al, 2004). The contact surface has been interpolated in 3D with the DSI methods, which it is based on the outcrop curve, foliation and axis orientation/plunge data, according to the procedure described in Le Carlier de , Salles et al (2011), andCaumon et al (2009).…”
Section: Appendix A: 3d Modelling Approach With the Gocad 3d Modellermentioning
confidence: 99%
“…The 3D model was built from available field data (Albussaïdi and Laval, 1984;Callec, 2001;Puigdefàbregas et al, 2004;Salles et al, 2011), taking into account three faults, including the Rouaine fault, in a domain of interest limited by the Ourgues fault towards the East. Two scalar fields were interpolated to model this Tertiary depocentre: one for members AeG, and another one for the Nummulitic Limestone and the Globigerina Marls (Fig.…”
Section: Model Descriptionmentioning
confidence: 99%